PENGGUNA OJEK ONLINE DI KALANGAN MAHASISWA UNIVERSITAS SAM RATULANGI MANADO - Tumuwe, Riswanto; Damis, Mahyudin; Mulianti, Titiek (HOLISTIK, Journal Of Social and Culture, 2018)
Transport used the society to facilitate daily activities. Everyone needs transportation in a variety of activities such as work, school, travel or other activities. Technological advances in the field of transportation, becoming the socio-cultural reality going on in the community, that the current internet is very influential to the citizens of the community in living the life the community. The rise of smartphone users, either the system android or iOS makes the community dependent on Smartphones and the internet. The opportunities for making business founder Taxi online (Go-Jek) is presenting an online-based. The phenomenon of online transportation currently being discussed, because warm-based booking applications are easily downloaded by users of smartphones good System android or iOS.The research method used was based on qualitative methods of study case as well as the collection of data is done with the techniques of observation, interview and documentation. The main source of data retrieved from the interview several students and drivers on the Unsrat campus environment. Results of the study showed that college students online taxi users greatly helped by using taxi online. Online taxi exploited students not only deliver them home leave, but also to order food and supplies for academic purposes with rates that are relatively inexpensive. This research is expected to contribute works of Ethnography about socio-cultural knowledge of students about the use of an online as well as can be a material input for Manado City Government in order to make the regulation of public transport based online, so as to advance the transportation services sector in the city of Manado.Keywords : transport, online, driver